Do International Human Right Ratifications Improve Respect For Human Right In Indonesia? - Liona Nanang Supriatna (Jurnal Hukum PRO JUSTITIA, 2007)
Do International Human Right Ratifications Improve Respect For Human Right In Indonesia?